Telehealth, sustainable economic development, and social welfare - Wang, Fuhmei (Technological and Economic Development of Economy, 2012)
Country experiences in Australia, New Zealand, Norway, Taiwan, and UK have been in favor of telehealth services since the early 1990s. Though a few studies do discuss evidence of the efficacy and cost-effectiveness of telehealth programs, the literature might limit to financial evaluation. This research investigates the welfare implications of conventional in-person and telecommunications health care as improving health levels or preventing health from deterioration for efficient resource allocation by incorporating government intervention for equal accessibility of health care in the economic progress perspective. Analytical findings indicate that the inverse U shape relationship between telehealth expenditure share and social welfare status exists as the nonlinear nexus between telehealth expenditure share and economic growth presents. The health dividend in terms of an enhanced economic growth rate can be achieved only when the initial share of telehealth expenditure is smaller than the growth-maximizing share. For economic sustainable development, telehealth initiatives strengthen rather than compete with conventional in-person health care. Research results guide the countries, which have or will have telehealth systems, for effectively allocating medical resources to stimulate economic growth and improve the population’s well-being.